Identification of suitable reference genes for gene expression studies in rat skeletal muscle following sciatic nerve crush injury - Wang, Xinghui (Mol Med Rep, 2019)
Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) is a molecular biological method used to assess gene expression characterized by high simplicity, effectiveness, specificity and sensitivity. The selection of a suitable reference gene for normalization is critical for the accuracy of quantitative results. Peripheral nerve injury is a common clinical disorder that affects multiple tissues and organs, including peripheral nerves, neurons and the innervated muscles. Numerous genes are differentially expressed in skeletal muscles during muscle denervation and reinnervation following peripheral nerve injury. The identification of a suitable reference gene in innervated muscles following nerve injury may improve the understanding of the alterations in gene expression in the processes of peripheral nerve repair and regeneration. Therefore, in the present study, by using a rat sciatic nerve crush model, the expression levels of various housekeeping genes were examined. In particular, the expression levels of 13 housekeeping genes, including 18S ribosomal RNA, actin β, ankyrin repeat domain 27, cyclophilin A, GAPDH, hypoxanthine phosphoribosyltransferase 1 (HPRT1), mitochondrial ribosomal protein L10, phosphoglycerate kinase 1, RPTOR independent companion of mammalian target of rapamycin complex 2, TATA-box binding protein, ubiquitin C, UBX domain protein 11 and tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein ζ, were investigated in gastrocnemius muscles. The geNorm and NormFinder analyses suggested that the expression level of HPRT1 was particularly stable in gastrocnemius muscles following rat sciatic nerve crush injury. Therefore, HPRT1 may be used as a reference gene for the normalization of gene expression data generated by RT-qPCR.